2007
DOI: 10.2193/2006-422
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Advantages for Common Loons Using Rafts

Abstract: Artificial nesting islands, or rafts, are often deployed in common loon (Gavia immer) breeding territories to decrease negative impacts of mammalian predation and water‐level fluctuations on nesting success. The management value of rafts has been demonstrated in other studies; however, no published studies have quantified the use or associated reproductive benefits of rafts on lakes exhibiting water‐level fluctuations. These lakes constitute a major portion of loon nesting habitat in New England and the Midwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Anthropogenic disturbances that affect loons on the breeding lakes include habitat degradation from shoreline development, encroachment of buildings on traditional nesting sites, decreased water clarity from erosion and surface runoff, nutrient enrichment, increased predator densities, changes in fish species composition, and increased human recreational activity (Titus and VanDruff 1981, Heimberger et al 1983, Jung 1991, Newbrey et al 2005, Desorbo et al 2007, Found et al 2008. Lake acidification, accidental ingestion of lead fishing tackle, and bioaccumulation of environmental contaminants such as methylmercury are other significant stressors threatening loon productivity and overall fitness (Barr 1986, Alvo et al 1988, Meyer et al 1998, Kamman et al 2005, Evers et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic disturbances that affect loons on the breeding lakes include habitat degradation from shoreline development, encroachment of buildings on traditional nesting sites, decreased water clarity from erosion and surface runoff, nutrient enrichment, increased predator densities, changes in fish species composition, and increased human recreational activity (Titus and VanDruff 1981, Heimberger et al 1983, Jung 1991, Newbrey et al 2005, Desorbo et al 2007, Found et al 2008. Lake acidification, accidental ingestion of lead fishing tackle, and bioaccumulation of environmental contaminants such as methylmercury are other significant stressors threatening loon productivity and overall fitness (Barr 1986, Alvo et al 1988, Meyer et al 1998, Kamman et al 2005, Evers et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Such first-year drops in productivity in these studies might be a consequence of a short-term increase in aggressive behavior similar to what we observed among males within this study. Because platforms have been shown to increase the long-term reproductive success of historically unproductive territories over longer periods of time (Piper et al 2002;DeSorbo et al 2007), apparently the short-term consequences of heightened aggressive behavior and reduced productivity are outweighed by the long-term benefits of enhanced reproductive success in loons. Such long-term fitness benefits would explain why territorial escalation in response to enhancement of nesting habitat would be adaptive.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, loons have experienced significant loss of nesting habitat because of an increase in shoreline development and human recreation (McIntyre and Barr 1997). Consequently, conservationists have employed artificial platforms, which protect nests from terrestrial predators and water-level fluctuations, to help maintain loon populations (Mathisen 1968;McIntyre and Mathisen 1977;Sutcliffe 1979;Piper et al 2002;DeSorbo et al 2007). However, Wright and Taylor (2000) suggested that nesting platforms might increase aggressive interaction, which, in turn, could decrease juvenile and adult survivorship (see Caro 1998;Anthony and Blumstein 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For New Hampshire, we estimated reproductive parameters using data from 159 lakes monitored at least once during 1990 to 2004. Surveys of previously occupied and suitable habitat were conducted by staff biologists from May to August, and the number of chicks raised to mid-August was recorded for each territory (DeSorbo et al 2007). To estimate m from these data, we used a mixed-effects model to account for repeated annual observations of specific loon territories in the data set ( Fig.…”
Section: Annual Fecunditymentioning
confidence: 99%
“…Potential explanations for changes in population growth include impacts from summer tourism (Robertson andFlood 1980, Hemberger et al 1983), land-use change (Lindsay et al 2002), acid deposition (DesGranges and Darveau 1985, Parker 1988, McNicol et al 1995, mercury toxicity (Fimreite 1974, Kenow et al 2007, and lead poisoning from fishing tackle Chafel 1992, Pokras et al 1998). These and lesser known problems associated with water level management (DeSorbo et al 2007), changes in availability of forage fish, fishing net entanglement (Smith and Morgan 2005), coastal oil spills (Ken Munney, United States Fish and Wildlife Service, personal communication; also see Environment Canada 2007), and disease (Brand et al 1983(Brand et al , 1988Moccia 2005) may affect specific vital rates either directly or through interactions with one another. Alternately, or in addition, changes in population growth may indicate the increasing influence of density-dependent factors as loon populations recovered from lows in the mid 1990s.…”
mentioning
confidence: 99%